(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The chltinase aeth·ity of thebacterial isolates were detennfned, and it was found that the isolae S.marcescens HL-165 has the highest acitivity in degradation of crJtin gi...ing ma.’dmumartivity of chitinase (0.894 U ml)-l m the seventh day of inocubation, then the isolate B. Licheniformis ISR -75 which gave maximum activity (0.486 u ml)-l in the fowih day of inocubation, the isolate B, mycodides CH-45 occpied the third degree giving ma.ximum activity (0.346 U ml)-l it, the ninth day of inocubation, whereas the isolate. Streptomyces spp. Act-14 has the lowest activity ghing maximum acthity (0.240 U ml)-l in the twelfth day of inocubation, in colloidal chitin medium. It was found the isolate B. Licheniformis ISR"5 prnduced chitinase when grown at 50 C in chitin broth medium whereas ihe other Bad’erial isolates produced this enzYlIle when they grown at (28-30) C i.n the same medium.